Distribution and predictors of non-indigenous marine species within South Africa's MPA network - Brooker, Ben (Department of Biological Sciences, 2016)
Considering the continual dissemination of marine non-indigenous (NIS) species across biogeographic borders, little is known about the status of these species within the network of South African marine protected areas (MPAs). Using the most recent data, a target list of NIS was set up for each MPA. Nineteen of the 23 South African MPAs were surveyed intertidally for alien and invasive species. The intertidal zone was divided into high-, mid- and low-shore and surveys were conducted during spring low tide. The presence and location in the intertidal zone of alien and invasive species were recorded. Additionally, invasive species' biomasses were quantified at sites at which they were found. Classification and regression tree (CART) analysis was used to assess which factors result in high numbers of NISs within MPAs. The invasive Mediterranean mussel, Mytilus galloprovincialis, was the most widespread species, occurring in 13 of the 19 sampled MPAs. It was most prominent on the island MPAs of the West Coast National Parks and had an overall highest biomass in the mid-shore. The bryozoan, Bugula dentata, was also widespread - present in MPAs across all three ecoregions. The invasive acorn barnacle, Balanus glandula, and bisexual mussel, Semimytilus algosus, both exhibited high levels of invasion in MPAs on the west coast. Extensions of known ranges were recorded for a number of species: the bryozoans Bugula dentata, Watersipora subtorquata and Cryptosula pallasiana, the polychaete Neodexiospira brasiliensis, the amphipod Orchestia gammarellus and the hydrozoan Obelia dichotoma. Certain species were recorded outside of harbours for the first time: the hydrozoans Obelia dichotoma and Obelia geniculata, the bryozoan Cryptosula pallasiana and the ascidians Microcosmus squamgiger and Diplosoma listerianum. CART analysis indicated that the size of the nearest port was an important indicator of the number of alien species in an MPA. When the nearest port is bigger than 0.4 km², more alien species are likely to occur within that MPA. For invasive species, the distance to the nearest yacht marina was the most important factor, with MPAs within 3.7 km of a yacht marina being more likely to have more invasive species in their borders. For all NISs, the highest numbers in an MPA were expected when the nearest port was greater than 2.1 km² and the nearest yacht marina was within 3.7 km of that MPA. Using these findings, spatial planning of future MPAs can further be prioritised to minimise the risk of introduction and spread of NIS therein. MPAs at risk as defined by these findings require structured monitoring regimes. A proactive measure would be establishing an interdisciplinary forum between relevant management authorities in order to enable dissemination of information on NIS. While controlling established NIS is difficult, the creation of task groups to act as rapid response teams for NIS, and the possibility of small-scale fisheries from edible invasive species are practical avenues that could be explored as mitigation efforts.